Market Power in Interactive Environmental and Energy Markets: The Case of Green Certificates - Eirik S. Amundsen; Gjermund Nese (Center for Economic Studies and ifo Institute (CESifo), 2016)
Markets for environmental externalities are typically closely related to the markets causing such externalities, whereupon strategic interaction may result. Along these lines, the market for Tradable Green Certificates (TGCs) is strongly interwoven in the electricity market as the producers of green electricity are also the suppliers of TGCs. In this paper, we formulate an analytic equilibrium model for simultaneously functioning electricity and TGC markets, and focus on the role of market power. We consider a Stackelberg leadership model with endogenous treatment of the interaction between the electricity and the TGC markets. One result is that a certificate system faced with market power may collapse into a system of per unit subsidies as the producers involved take account of the joint functioning of markets. Furthermore, our analytical model shows that TGCs may be an imprecise instrument for regulating the generation of green electricity.
Keywords: C70; Q28; Q42; Q48; 330; renewable energy; electricity; Green Certificates; market power